Utilizing Baidu Index Data to Investigate the Spatiotemporal Characteristics of Public Concern towards Lifelong Education - Tan, Qinyi; Ao, Yang; Teng, Luyan (Quality in Sport, 2024)
Background and purpose: With the advancement of Industry 4.0 and the vigorous development of the Internet, search engines have become one of the important platforms for the public to obtain information. As the world's largest Chinese search engine, Baidu is widely popular with the Chinese public. Similar to Google Trends, the Baidu Index is one of the most important databases on the Internet and even in the entire data age. This study adopted the Baidu Index to investigate the public's attention to "Lifelong Education" and analyze its changing trend and geographical distribution, to grasp the public's attention to it in a more comprehensive way. Materials and methods: The Baidu Index was used to obtain the attention of the keyword “Lifelong Education" from July to November 2023. The characteristics of attention are analyzed from three aspects: trend research, demand graph, and user portrait. Finally, it focuses on the comparison between the keyword "Lifelong Education" and the related word "Lifelong Education Platform". Results: The term "Lifelong Education" showed two fluctuations during the period, both of which showed an initial rise and then a decline. For the demand graph, the public pays the most attention to "Lifelong Education Platform", "Lifelong Learning" and "Compulsory Education". The group that pays more attention to "Lifelong Education" is mainly distributed in East China, mostly female, 20~29 years old. Conclusion: Similar to Google Trends, the Baidu Index is a useful tool to study the trend of keyword searches, insight into the change in netizens' demand and monitoring the trend of media public opinion. <span data-slate-node="text" data-slate-fragment="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">The results show that the main reasons for the two obvious changes in search volume are that the National Open University of China opens freely lifelong education platform and provides free and comprehensive learning resources, and "Lifelong Education" appears as a translation in the National College English Test Band 4 (CET-4) in June 2023.